Lobbying, corruption and other banes - Nauro F. Campos; Francesco Giovannoni (Institute for the Study of Labor (IZA), 2008)
Although the theoretical literature often uses lobbying and corruption synonymously, the empirical literature associates lobbying with the preferred mean for exerting influence in developed countries and corruption with the preferred one in developing countries. This paper challenges these views. Based on whether influence is sought with rule-makers or rule-enforcers, we develop a conceptual framework that highlights how political institutions are instrumental in defining the choice between bribing and lobbying. We test our predictions using survey data for about 6000 firms in 26 countries. Our results suggest that (a) lobbying and corruption are fundamentally different, (b) political institutions play a major role in explaining whether firms choose bribing or lobbying, (c) lobbying is more effective than corruption as an instrument for political influence, and (d) lobbying is more powerful than corruption as an explanatory factor for enterprise growth, even in poorer, often perceived as highly corrupt, less developed countries.
urn:nbn:de:101:1-2008100949
Keywords: E23; 330; Lobbying; corruption; political institutions; Institutionalismus; Institutionelle Infrastruktur; Interessenpolitik; Korruption; Entwicklungsländer; Industriestaaten